2018
DOI: 10.1002/ece3.4080
|View full text |Cite
|
Sign up to set email alerts
|

Traits correlate with invasive success more than plasticity: A comparison of three Centaurea congeners

Abstract: The importance of phenotypic plasticity for successful invasion by exotic plant species has been well studied, but with contradictory and inconclusive results. However, many previous studies focused on comparisons of native and invasive species that co‐occur in a single invaded region, and thus on species with potentially very different evolutionary histories. We took a different approach by comparing three closely related Centaurea species: the highly invasive C. solstitialis, and the noninvasive but exotic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…When tested in common garden experiments, invasive plants, from their nonnative ranges, often grow larger than conspecifics from the native range (van Kleunen et al 2010, Maron et al 2014) suggesting that natural selection is acting on these and related traits during exotic invasion (but see Rosche et al 2019). Our results for inter‐range differences for the three congeners are consistent with results reported in other studies for the same studied species (Graebner et al 2012, García et al 2013, Sotes et al 2015, Filipe and Montesinos 2016b, Montesinos and Callaway 2018, Montesinos et al 2019, Hierro et al 2020), and are consistent with other comparisons of soils from European and American populations of C. solstitialis , which generally support soil‐related enemy release (Hierro et al 2006, Andonian et al 2011, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When tested in common garden experiments, invasive plants, from their nonnative ranges, often grow larger than conspecifics from the native range (van Kleunen et al 2010, Maron et al 2014) suggesting that natural selection is acting on these and related traits during exotic invasion (but see Rosche et al 2019). Our results for inter‐range differences for the three congeners are consistent with results reported in other studies for the same studied species (Graebner et al 2012, García et al 2013, Sotes et al 2015, Filipe and Montesinos 2016b, Montesinos and Callaway 2018, Montesinos et al 2019, Hierro et al 2020), and are consistent with other comparisons of soils from European and American populations of C. solstitialis , which generally support soil‐related enemy release (Hierro et al 2006, Andonian et al 2011, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…However, most of such studies have focused on exotic species that are deemed invasive, without comparisons to less‐successful exotic species that only naturalize in the same nonnative ranges (but see Kulmatiski et al 2008). The few studies that have compared invasive and non‐invasive exotic congeners, in other contexts, indicate that many non‐invasive exotics have many of the same putatively adaptive traits in the nonnative range as highly invasive species (Gerlach and Rice 2003, García et al 2013, Montesinos and Callaway 2018). This limits the logical inference for invasive success that is derived from simply possessing particular signs of local adaptation by an invasive species, and raises questions about the importance of soil biota in the success (or lack thereof) of exotic non‐invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that some invasive plants developed more competitive traits including greater fertility[61] and higher abundance of chemical weapons[62]. The importance of the role of phenotypic plasticity for successful invasions is exceeded by the development of novel heritable traits in the invasive population [63, 64] that ultimately result in more competitive invaders [65]. Therefore, studies of the pathway of plant introduction are critical for prediction and prevention of future introductions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Field-based trait measurements can determine how plants respond to environmental change in situ but cannot discriminate between phenotypically plastic versus genetic responses to local conditions (Montesinos and Callaway 2018;Brandenburger et al 2019a). For invasive species, adaptive genetic responses in their introduced ranges can be identified using common garden experiments, whereby seeds sourced from native and introduced locations are propagated and grown under standard conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%